Modeling the dispersion of viable and total Escherichia coli cells in the artificial semi-enclosed bathing area of Santa Marinella (Latium, Italy). Issue 1 (15th June 2015) - Bonamano, S.; Madonia, A.; Borsellino, C.; Stefanì, C.; Caruso, G.; De Pasquale, F.; Piermattei, V.; Zappalà, G.; Marcelli, M.
Highlights: E. coli dispersion in Santa Marinella bathing area was evaluated during summer season. E. coli was counted by Culture-Based and Fluorescent Antibody methods. Two modeling approaches were performed to simulate both living and total cells. MPRA and flushing time give details to physical and biological processes dominance. They evaluate the reduction of bacterial dispersion caused by the artificial barriers. Abstract: Coastal areas are strongly affected by episodes of fecal contamination due to polluted water inflows from inadequately treated sewages. The present study aims to investigate the dispersion of Escherichia coli in the artificial semi-enclosed bathing area of Santa Marinella (Latium, Italy) through in situ samplings carried out in summer 2012 and the application of a dynamic model. Collected samples were analyzed by the Culture-Based technique and the Fluorescent Antibody method in order to estimate both the viable culturable cells and the total E. coli population, respectively. The in situ datasets were used to test the proposed modeling approach and simulate the behavior of bacteria as particles subjected, or not, to decay. Next, the flushing time and the computation of the Microbiological Potential Risk Area allowed the evaluation of the contribution of physical and biological processes to coliform dispersion and the related potential risk for bathers.